Marketing Intelligence Implementation for Supply Chain Mannagemnt of Mix Products That Affect the Purchasing Decision on Citra Karisma, Yogyakarta - Iis Noviyanti; N. Lilis Suryani; Nurmin Ariant; Lia Asmalah (International Journal of Supply Chain Management, 2020)
Abstract. The purposes of this study was to determine the implementation of marketing intelligence to the supply chain management and mix product that had impact on purchasing decisions on Citra Karisma, Yogyakarta. This was a descriptive quantitative research. The population of this research was the prospective consumers of Citra Karisma during 2020 with the sample were 116 respondents. The Non-probability sampling technique, namely incidental sampling technique was used. The data collection method in this study was a questionnaire and the data analysis method was descriptive analysis and path analysis. Each area of supply chain management requires different MI support. Management firms need to focus on relationships with suppliers and the movement and storage of goods to maximize profitable outcomes while minimizing risks and costs. The result of path analysis indicated that the marketing intelligence variable affected the supply chain and mix products which had influence on the purchasing decision while marketing intelligence had influence on the purchasing decision through supply chain with the effect of 43.10%.